(untitled) (Biocenosis, 2024)
The gardens that attract hummingbirds in Los Santos region of Costa Rica promote scientific tourism, species conservation and the enjoyment of nature. The interaction between plants and hummingbirds is key to the survival of these birds, to plant diversity through pollination and to ecological balance. Therefore, when designing gardens, it is essential that the selection of plants be carried out according to technical-scientific principles to ensure its success. Recommendations are based on factors such as plant physiology and climatic impacts so as to encourage people to create and maintain these spaces. Additionally, the relevance of documenting interactions is emphasized to improve the effectiveness of the garden and contribute to scientific knowledge. Guidelines are also proposed for garden design, considering elements such as soil, water, and the surrounding environment. With careful planning based on technical and scientific data, gardens can become sanctuaries that promote the care and responsable use of the natural environment.